INDIVIDUALIZATION FACTORS OF STUDENTS’ PHYSICAL EDUCATION AT MODERN STAGE OF ITS REALIZATION - V.A. Druz; S.S. Iermakov; G.P. Artemyeva; Y.I. Puhach; R. Muszkieta (Physical Education of Students)
Purpose: determination of main conditions for complying individual potentials of physical condition and students’ physical fitness for practicing appropriate kind of sports. Material: In the research students attending sport circles participated (n=960). Sport qualification of the participants was in the range from beginners to international masters of sports. The contingent of the tested consisted of different age groups and sport specializations. Results: for satisfaction of students’ individual interests to definite kinds of sports it is necessary to have professional graphs of motor functioning in sports and ergo-graphic characteristic of competition exercises. Students shall have information about their physical condition and physical fitness. Besides, it is necessary to have the data about students’ current physical condition, which determines students’ workability. Passport data about medium of motor functioning and individual’s physical potentials permit to find adequacy of combining and success of object-medium interaction. It results in enthusiasm in practicing certain kind of sports. Conclusions: The presence of adequate compliance between determined analytical links of physiological processes of individual’s adaptive behavior and requirements to the chosen medium of sport functioning permits to maximally effectively solve the problems of students’ physical education’s individualization.